Herbage Mass Productivity, Composition, and Biological Compatibility of Oat and Vetch Mixture at Different Seed Rate Proportions in Abandoned Lands - Shanker Raj Barsila; Shiva Acharya; Prashiksha Acharya (International Journal of Agronomy, 2024)
The grass-legume intercropping systems have become one of the alternative practices to increase the herbage dry matter yield and quality and to enhance resource usage. The study evaluated the competitiveness of various oat/vetch seed rate proportions using a randomized complete block design (RCBD) with five treatments, replicated five times. Fresh herbage was harvested above the ground and subjected to estimate its dry matter productivity, along with the proximate and fibre compositions were estimated. Relative yield (RY), relative total yield (RYT), relative crowding coefficient (RCC), and aggressivity index (AI) were calculated from the dry matter yield of oats and vetch. The monoculture of oats (100% oats) had the highest herbage DM productivity (5.98 t/ha) similar to the mixed oat/vetch mix plots. The vetch monoculture (100% vetch) and 50 : 50 oat/vetch seed rate proportions had a higher CP content than the oat monoculture (100% oat). The total ash (TA) content was considerably higher for 100% oats and the 75 : 25 oat/vetch mixture, respectively. The ether extract was higher for either of the monocultures of oat and vetch. The neutral detergent fibre (NDF) and acid detergent fibre (ADF) content remained highest at 25 : 75 oat/vetch, while the NDF content was lowest at 100% vetch. The ADF content was the lowest for 50 : 50 oat/vetch. Relative yield (RY) and the relative crowding coefficient (RCC) showed an advantage in yield for 50 : 50 oat/vetch seed rate proportions for dry matter yield. However, oat was more aggressive than vetch in the mixture, except in 25 : 75 oat/vetch. It was confirmed that the 50 : 50 seed rate proportions of oat/vetch could be a promising option to reduce the bulkiness of the oat. Moreover, long-term comparative studies on agronomic performance of the oat/vetch seed proportions in conventional and abandoned lands are recommended to establish persistent results for oat/legume mixed cropping system.